THE CORRELATION BETWEEN FREQUENCY OF TRAINING AND INTEREST IN LISTENING ENGLISH SONG TOWARD THE ACHIEVEMENT IN LISTENING AMONG THE SECOND YEAR STUDENTS OF SMAN 8 KEDIRI - Maftoh, Mohammad (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study was aimed at investigating whether there is significant and simultaneous correlation among frequency of training and interest toward the achievement in listening among the student of SMAN 8 Kediri. This research implemented correlational research design. 100 students of second grade of SMAN 8 Kediri were used as the sample of research. Questionnaire and teacher’s document were used as the instrument of the research. Questionnaire was used to measure students’ frequency of training and interest, while document was used to collect the data of students’ listening achievement. The data were analyzed using regression analysis to find the significant and simultaneous correlation among the three variables. The data analysis was computed using Statistical Package for Social Sciences (SPSS) version 11.0. The results showed that there is significant and simultaneous correlation between frequency of training and interest in listening English song toward the achievement in listening among the second year students of SMAN 8 Kediri.